Chemoprevention of spontaneous ovarian cancer in the domestic hen - Mocka, E. H. (Poult Sci, 2017)
The hen is an attractive animal model for in vivo testing of agents that thwart ovarian carcinogenesis because ovarian cancer in the domestic hen features clinical and molecular alterations that are similar to ovarian cancer in humans, including a high incidence of p53 mutations. The objective of the study was to test the potential ovarian cancer chemopreventive effect of the p53 stabilizing compound CP-31398 on hens that spontaneously present the ovarian cancer phenotype. Beginning at 79 wk of age, 576 egg-laying hens (Gallus domesticus) were randomized to diets containing different amounts of CP-31398 for 94 wk, 5 d, comprising a control group (C) (n = 144), which was fed a diet containing 0 ppm (mg/kg) of CP-31398; a low-dose treatment (LDT) group (n = 144), which was fed a diet containing 100 ppm of CP-31398; a moderate-dose treatment (MDT) group (n = 144) which was fed a diet containing 200 ppm of CP-31398; and a high-dose treatment (HDT) group (n = 144), which was fed a diet containing 300 ppm of CP-31398. Hens were killed at 174 wk of age to determine the incidence of ovarian and oviductal adenocarcinomas. Whereas the incidence of localized and metastatic ovarian cancers in the MDT and HDT groups was significantly lower (up to 77%) compared to levels in the C and LDT groups (P < 0.05), the incidence of oviductal cancer was unaffected by CP-31398. CP-31398 appears to be an effective tool for chemoprevention against ovarian malignancies, but does not appear to affect oviductal malignancies.